2019
DOI: 10.5114/aoms.2018.80362
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival of patients with EGFR mutation-positive non-small-cell lung cancer treated with erlotinib, gefitinib or afatinib under drug programmes in Poland – Real-World Data

Abstract: The aim of the study was to estimate the overall survival of patients with EGFR mutation-positive non-small-cell lung cancer treated with erlotinib, gefitinib or afatinib. Material and methods: Real-world patients who received afatinib, erlotinib or gefitinib between 1 July 2012 and 30 October 2017 were analysed in five subgroups. Results: Among 267 patients treated with afatinib financed as the first line of treatment, 76 (28.46%) deaths occurred. Median observation time was 12.8 months (95% CI: 11.2-13.9). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The differences of deletion rate of the enzyme cytochrome P450 2A6 (CYP2A6), an enzyme involved in the metabolism of tobacco carcinogens, is high among Malays (35.2%) followed by Chinese (18.3%) and Indians (7.1%) [ 19 ]. Using real-world data from Poland, Brzozowska et al confirmed the clinical efficacy of tyrosine-kinase inhibitors (TKIs), but the survival results are lower compared to clinical studies from Asian populations [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences of deletion rate of the enzyme cytochrome P450 2A6 (CYP2A6), an enzyme involved in the metabolism of tobacco carcinogens, is high among Malays (35.2%) followed by Chinese (18.3%) and Indians (7.1%) [ 19 ]. Using real-world data from Poland, Brzozowska et al confirmed the clinical efficacy of tyrosine-kinase inhibitors (TKIs), but the survival results are lower compared to clinical studies from Asian populations [ 20 ].…”
Section: Discussionmentioning
confidence: 99%